Development of a Newly Designed Combined Grinding Equipment - Gan, Hui Leng; Law, Hoon Chit; R. A., Bakar (2014)
As acknowledged, biomass has been identified as the most promising alternative replacing fossil fuel due to its sustainability. Grinding is known to be essential to reduce size of biomass samples to produce products with enhanced strength and durability. Some of the commonly used devices include hammer mill and knife mill. With known importance, a grinding equipment has been designed and fabricated. However, the first prototype of the grinding facility resulted in irregular shape and sizes of the specimens, and consequently reducing the quality of the ground products obtained. This phenomenon therefore prompted the necessity to design a new facility. This paper thus discusses the development of the improved version of the grinding facility from the existing one through the incorporation of better functions. The improved version of the facility was utilised powerful cutting blades with both shearing and hammering functions which produced more uniformed and fine particles. A specially designed specimen collector was also added to the facility to reduce dust contamination. The assembled facility was utilised to test on biomass resources like Jatropha fruits and oil palm stems. Through manipulation of control parameters like cutting speed and operating time, the fineness of the particles could be varied, as appropriate.